Makna dan Fungsi Majaz dalam Pujian Kepada Nabi Muhammad SAW: Implikasi bagi Pendidikan Agama Aswaja - Nurul Khofifah; Alfiana Rahma Maulida; Anisa Aulia Febrianti (Yayasan Mutiara Hati Moeslem, 2026)
Praise for the Prophet Muhammad (peace be upon him) within the Ahlussunnah wal Jamaah (Aswaja) tradition extensively employs majaz (figurative language) as a rhetorical device to convey profound spiritual and educational meanings. However, studies that specifically examine majaz in prophetic praise and its implications for Islamic religious education remain relatively limited. This study aims to analyze the meanings and functions of majaz in selected texts of praise for the Prophet Muhammad and to examine their implications for Islamic religious education within the Aswaja tradition. This research adopts a qualitative library research method, employing a balaghah analysis of representative prophetic praise texts, examined from the perspective of Aswaja-based Islamic education. The data were analyzed using descriptive-analytical techniques to identify the types, meanings, and functions of majaz and their educational relevance. The findings indicate that majaz in prophetic praise functions not only as an aesthetic linguistic element but also as an effective medium for internalizing love for the Prophet, strengthening faith, and instilling values of moderation and tolerance that characterize the Aswaja tradition. The study concludes that the use of majaz in praise of the Prophet can enrich Islamic religious education, enhance learners’ religious motivation, and contribute to the formation of a moderate and inclusive character grounded in the teachings of the Prophet Muhammad.